Digital signal processing - Proakis, John G.; Manolakis, Dimitris G. (Chennai: Pearson India Education, 2024)
"This book was developed based on our teaching of undergraduate- and graduate-level courses in digital signal processing over the past several years. In this book, we present the fundamentals of discrete-time signals, systems, and modern digital processing as well as applications for students in electrical engineering, computer engineering, and computer science. The book is suitable for either a one-semester or a two-semester undergraduate-level course in discrete systems and digital signal processing. It is also intended for use in a one-semester first-year graduate-level course in digital signal processing"--
Includes bibliographical references and index.
Keywords: Signal processing -- Digital techniques